Implementing The Contextual Teaching and Learning (CTL) Method to Enhance English Proficiency in Early Childhood: A Study in Indonesian and Malaysian Kindergartens - Yulianti, Enny; Nuha, Ulin; Ab Wahab, Nursyuhada’; Ramalingam, Sangeeth (PIAUD Universitas Islam Negeri Sunan Kudus, 2024)
This study explores the application of the Contextual Teaching and Learning (CTL) method in teaching English to children aged 5–7 years in kindergartens across Indonesia and Malaysia. A qualitative approach was adopted, incorporating observation, interviews, and document analysis to investigate how the CTL method enhances children’s English language proficiency. Teachers implemented hands on activities, including conversations, daily instructions, and engaging tasks such as singing, shared reading, and project-based activities. The approach involved providing children with English storybooks and videos, delivering materials engagingly and enjoyably, and emphasizing a student-centered learning environment. Key strategies employed by teachers included establishing interconnected meanings, promoting conceptual understanding through real-life relevance, fostering group collaboration, and facilitating knowledge transfer to new contexts. Results revealed that 50 children were proficient in English speaking before using the CTL method, while 75 exhibited limited proficiency. After implementing the CTL method, the number of proficient children increased to 95, while those with limited proficiency decreased to 30. These findings highlight the effectiveness of the CTL method in improving children’s English-speaking skills. The study concludes that employing the CTL method through a qualitative approach significantly enhances early childhood English proficiency by incorporating contextual, enjoyable, and relevant learning experiences aligned with young learners’ daily lives.